Upaya Meningkatkan Kemampuan Memakai Sepatu Bertali Melalui Analisis Tugas pada Mata Pelajaran Bina Diri Pada Anak Tunagrahita Ringan Kelas II di SLB Asuhan Kasih Kota Kupang - Nggadi, Intan May; Selan, Ot Bil Wilson; Wangge, Vinsesnsius; Ajito, Timoteus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the ability of mildly intellectually disabled children in Grade II at SLB Asuhan Kasih, Kupang City, to wear lace-up shoes through Task Analysis in the Personal Development subject. Children with special needs are entitled to education, including the development of self-help skills, self-care, and self-management. Observation results indicated that mildly intellectually disabled students faced difficulties in wearing lace-up shoes, particularly in understanding the steps and coordinating hand movements. This Classroom Action Research (CAR) involved 3 Grade II students (MRR, PPJ, PVS). The results of Cycle II showed a significant improvement, where all subjects reached the Very Good category (scores 85-95), after previously being in the Very Poor category (scores 30-40) during the pre-test. The conclusion of this study is that the use of lace-up shoe media can enhance students' ability and concentration in wearing lace-up shoes